The plasmidome of multidrug-resistant emergent Salmonella serovars isolated from poultry - Galetti, Renata; Casarin Penha Filho, Rafael Antonio [UNESP]; Ferreira, Joseane Cristina; Varani, Alessandro M. [UNESP]; Sazinas, Pavelas; Jelsbak, Lars; Costa Darini, Ana Lucia (Elsevier B.V., 2021)
The rapid emergence of resistant bacteria is occurring worldwide. The understanding of the dissemination of antimicrobial resistance using high-throughput sequencing and bioinformatics approaches is providing valuable insights into the genetic basis of the horizontal gene transfer and the emergence of the antibiotic resistance threat. This ultimately can offer vital clues to the development of coordinated efforts to implement new policies to continue fighting against bacterial infections. The poultry microbiota is characterized as a potential reservoir of resistance genes, mostly derived from the Enterobacteriaceae which have become increasingly important in human and animal infections. In this work, complete genome sequences were achieved for four multidrugresistant Salmonella spp. isolated from poultry from different farms in Brazil. We identified highly similar IncHI2-ST2 megaplasmids (larger than 275.000 bp) in all Salmonella isolates studied. These megaplasmids carry a resistome comprised of eleven different resistance genes (aac(6?)-Iaa, aadA1b, aph(4)-Ia, aph(6)-Id, aph(3?)-Ib, aph(3?)-Ia, aac(3)-Iva, sul1, tetA, tetB and dfrA1b) and four heavy metal tolerance operons (telluride, mercury, silver and copper). In conclusion, the multidrug-resistant plasmids identified in S. enterica serovar Schwarzengrund and Newport isolated from poultry show a variety of antibiotic resistance and heavy metal tolerance genes, providing advantages for the bacteria to survive under extremely unfavorable conditions.
Keywords: Plasmids; Antibiotic resistance; Heavy metal tolerance; Poultry